(untitled) (PYC Nepal Journal of Management, 2018)
This paper examines the gender differences in financial decision-making of university students who are young, single, childless individuals that have at least average financial literacy and very small or no income. This paper is based on the survey questionnaires developed by Grable and Lytton (2003), distributed and collected from 100 students (50 men and 50 women) by using convenience sampling technique. The study finds that men and women differ in their financial decision. Women are less risk taker than men in financial decision-making; it indicates that women prefer to safer investment.